Novel Eu-MOF-based mixed matrix membranes and 1D Eu-MOF-based ratiometric fluorescent sensor for the detection of metronidazole and PA in water. (January 2022) - Yu, Haihuan; Liu, Qun; Fan, Mingyue; Sun, Jing; Su, Zhong-Min; Li, Xiao; Wang, Xinlong
Abstract: Metal organic framework-based mixed matrix membranes and ratiometric fluorescent sensors have received significant attention in application of sensing. Herein, a two-dimensional europium-based metal organic frameworks, [Eu(L-N2)2 ·(L-Cl4)1.5 ·H2 O] (CUST-506) . (L-Cl4 = 2, 3, 5, 6-tetrachloroterephthalic acid, L-N2 = 1, 10-phenanthroline) has been synthesized and characterized. Then, by immobilizing water-stable CUST-506 into agarose hydrogels, the Eu-MOF-based mixed matrix membranes (CUST-506-based MMMs ) were successfully prepared. The CUST-506-based MMMs exhibit not only the integrity and the metronidazole, picric acid (PA) sensing nature of Eu-MOF powder, but also excellent processability. Moreover, the Eu-MOF-based MMMs show distinguished water-stability. More interestingly, during the hydrothermal synthesis process, through anchoring the formic acid into the framworks to break the symmetrical coordination environment of the CUST-506, a one dimensional (1D) compound {[Eu(L-N2)·(L-Cl4)0.5 (COOH)·2H2 O]·(L-Cl4)0.5 }(CUST-507) with two emission centers from Eu 3+ -based centers and free L-Cl4 molecules is generated. CUST-507 displayes a unique ability of auto-calibration effect based on the dual emission mechanism and sensitive sensing of metronidazole and picric acid. This work highlights a simple fabrication strategy for MOF-based mixed matrix membranes and overcomes the environmental interference for ratiometric fluorescent sensor. Graphical abstract: Image 1 Highlights: Two novel Eu-based MOFs were constructed by anchoring functionalized and rigid ligands onto its skeleton. The 2D Eu-MOF-based mixed matrix membranes was prepared by encapsulating CUST-506 into agarose for the detection of metronidazole and picric acid. A 1D Eu-MOF-based ratiometric fluorescent sensor for the detection of metronidazole and picric acid. The two fluorescent sensor can detect the analytes in a water environment.